Brain Dominance and its Relationship to Creative Thinking among University Students in Jordon in the Light of Some Demographic Variables - Abdelhaq , Zahria; Al-Ajeli, Sabah (Jordan Journal of Educational Sciences, 2015)
The purpose of this study was to investigate the patterns of brain dominance among university students in Jordon, and their relationship to creative thinking, gender, grade level, and academic specialization. A cluster sample of (303) students participated in the study. The Hemisphere Dominance Inventory and Torrance Test of Creative Thinking were used for collecting data. The results of the study revealed that the left hemisphere dominance, followed by the integrated hemisphere dominance, were the most common types among students. There were significant differences in brain dominance due to the academic specialization variable, but no significant ones due to gender or grade level variables. The results also indicated that the creative thinking was correlated with the right and integrated hemisphere, but not with the left hemisphere; the mean of the right hemisphere subjects was significantly higher than left and integrated hemisphere subjects, and the mean of the integrated hemisphere subjects was higher than left hemisphere subjects in all creative thinking scores. These results highlight the importance of brain function in the learning-teaching process for the university students